2022
DOI: 10.1155/2022/1821684
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Reaction Time as a Marker of Executive Function Impairments in Fibromyalgia

Abstract: In addition to chronic widespread pain and depression and anxiety symptoms, patients with fibromyalgia frequently experience cognitive problems. This study investigated executive functions in fibromyalgia via a Go/No-Go task. To obtain comprehensive information about performance, traditional and ex-Gaussian parameters of reaction time (RT) variability were used, in addition to speed and accuracy indices. Ex-Gaussian parameters show an excellent fit to empirical RT distributions. Fifty-two female fibromyalgia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The result suggested that increased σ, which has been found to be related to impairment in the variability of typical RT responses [21] in the emotional condition is related to increased state anxiety in HPSA individuals. The effect is illustrated in the scatterplot in Figure 2 We observed a higher 𝜇 in the HPSA (560.3746, 20.60063 ms) compared to LPSA (536.4821, 20.60063 ms) group, in line with [7]. However, repeated measures ANOVA showed non-significant 𝜇 differences between both the HPSA and LPSA groups [𝐹 (1,22)=1.43780, partial ƞ 2 =0.03, 𝑝=0.243251].…”
Section: Ex-gaussian Analysis In the Emotional Stroop Experimentsmentioning
confidence: 67%
See 1 more Smart Citation
“…The result suggested that increased σ, which has been found to be related to impairment in the variability of typical RT responses [21] in the emotional condition is related to increased state anxiety in HPSA individuals. The effect is illustrated in the scatterplot in Figure 2 We observed a higher 𝜇 in the HPSA (560.3746, 20.60063 ms) compared to LPSA (536.4821, 20.60063 ms) group, in line with [7]. However, repeated measures ANOVA showed non-significant 𝜇 differences between both the HPSA and LPSA groups [𝐹 (1,22)=1.43780, partial ƞ 2 =0.03, 𝑝=0.243251].…”
Section: Ex-gaussian Analysis In the Emotional Stroop Experimentsmentioning
confidence: 67%
“…Previous studies have consistently reported higher ex-Gaussian 𝜇 values in those with multiple sclerosis (MS) [12], while higher σ values have been associated with individuals experiencing anxiety, potentially linked to attention bias [6]. Moreover, elevated τ values have been found in research focusing on subjects with ADHD [6], fibromyalgia [7] and anxiety [6]. These collective findings align with the hypothesis of our study, further supporting the notion that investigating the ex-Gaussian parameters can shed light on attention bias.…”
Section: Introductionmentioning
confidence: 99%
“…The majority (three in total; [ 9 11 ]) examined fibromyalgia syndrome (FMS), one of the prototypical chronic pain conditions characterized by widespread chronic pain and symptoms, such as fatigue, unrefreshing sleep, cognitive deficits, and comorbid emotional alterations (i.e., anxiety and depression) [ 12 , 13 ]. Concerning cognitive deficits, FMS patients tend to exhibit difficulties in verbal memory, organization and planning abilities, strategic planning, self-regulation, processing speed, attention, and cognitive flexibility [ 9 11 ]. The remaining studies explored chronic tension-type headache (CTTH) and rats with global cerebral ischemia [ 14 , 15 ].…”
mentioning
confidence: 99%
“…The first study [ 9 ], investigated executive functions in FMS patients compared with healthy controls via a Go/No-Go task. The variability of reaction time (RT)—by using traditional and ex-Gaussian parameters—was evaluated as a marker of executive function impairments.…”
mentioning
confidence: 99%